Continuous intraoperative optical coherence tomography-guided shield ulcer debridement with tuck in multilayered amniotic membrane transplantation - Sharma, Namrata (Indian J Ophthalmol, 2018)
PURPOSE: The aim of this study is to describe a modified surgical technique of continuous intraoperative optical coherence tomography (iOCT)-guided shield ulcer debridement with tuck-in multilayered Amniotic membrane transplantation (ML AMT) in vernal keratoconjunctivitis (VKC) with shield ulcer with plaque. METHODS: Seven eyes of seven patients presenting with VKC with shield ulcer with plaque were enrolled in this prospective case series and planned for shield ulcer debridement with ML AMT. Debridement of the ulcer base with double-layered AMT was done under the continuous guidance of iOCT. The main outcome measure was the time for complete reepithelialization. Statistical analysis was performed using the Stata-14.0 program for Windows. Data were presented as mean ± standard deviation/median (minimum-maximum) and frequency percentage as applicable. RESULTS: The surgery could be completed successfully in all cases and iOCT could provide real-time assessment of the depth of dissection during the entire procedure. The duration of complete healing and disintegration of amniotic membrane varied from 7 to 12 days. Recurrence was not seen in any case till 2 months follow-up. CONCLUSION: iOCT provides continuous monitoring of the depth of dissection and allows for a safe and complete debridement of the shield ulcer with plaque.